KulturConfusão : on German-Brazilian interculturalities - Finger, Anke K.; Kathöfer, Gabi; Larkosh, Christopher (Interdisciplinary German cultural studies, 2015)
"This collection examines cultural interactions between Germany and Brazil from the Early Modern period to the present day. The contributors represent various academic disciplines, including German Studies, Luso-Afro-Brazilian Studies, Cultural Studies, Linguistics, Art History and the social sciences. Their essays cover a wide range of works and media and offer a much-needed rethinking of the intercultural paradigm for the humanities."--